Phylogenetically diverse bacterial species produce histamine - Kristen A. Engevik; Amber Hazzard; Brenton Puckett; Kathleen M. Hoch; Sigmund J. Haidacher; Anthony M. Haag; Jennifer K. Spinler; James Versalovic; Melinda A. Engevik; Thomas D. Horvath (2024)
Histamine is an important biogenic amine known to impact a variety of patho-physiological processes ranging from allergic reactions, gut-mediated anti-inflammatory responses, and neurotransmitter activity. Histamine is found both endogenously within specialized host cells and exogenously in microbes. Exogenous histamine is produced through the decarboxylation of the amino acid L-histidine by bacterial-derived histidine decarboxylase enzymes. To investigate how widespread histamine production is across bacterial species, we examined 102,018 annotated genomes in the Integrated Microbial Genomes Database and identified 3,679 bacterial genomes (3.6 %) which possess the enzymatic machinery to generate histamine. These bacteria belonged to 10 phyla: Bacillota, Bacteroidota, Actinomycetota, Pseudomonadota, Lentisphaerota, Fusobacteriota, Armatimonadota, Cyanobacteriota, Thermodesulfobacteriota, and Verrucomicrobiota. The majority of the identified bacteria were terrestrial or aquatic in origin, although several bacteria originated in the human gut microbiota. We used liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based targeted metabolomics to confirm our genome discoveries correlated with L-histidine-to-histamine conversion in a chemically defined bacterial growth medium by a cohort of select environmental and human gut bacteria. We found that environmental microbes Vibrio harveyi, Pseudomonas fluorescens and Streptomyces griseus generated considerable levels of histamine (788 – 8,730 ng/mL). Interestingly, we found higher concentrations of histamine produced by gut-associated Fusobacterium varium, Clostridium perfringens, Limosilactobacillus reuteri and Morganella morganii (8,510––82,400 ng/mL). This work expands our knowledge of histamine production by diverse microbes.